Determinants of helmet use among health-care providers in urban India: Leveraging the theory of planned behavior - M N Shruthi; Anand D Meundi; D Sushma (Wolters Kluwer Medknow Publications, 2019)
CONTEXT: Wearing helmet during road traffic accidents among motorcycle riders decreases the likelihood of death by 39%. The theory of planned behavior (TPB), a psychological model helps to explain the failure in helmet usage, by assuming a causal chain. The current study was taken up as no studies have elicited the determinants of helmet usage in terms of TPB among health-care providers, the role models for healthful behavior by virtue of their profession in the current urban Indian context. AIMS: The aims of the study were (1) to determine the proportion of proper use of helmets and (2) to identify TPB-related factors and other factors influencing the use of helmets. MATERIALS AND METHODS: A cross-sectional study was conducted among 147 students and staff of a tertiary health-care center, Bengaluru, using a pretested, validated, semi-structured, self-administered questionnaire. Convenience sampling was used. Hierarchical regression model was used to explain variation in the scores of helmet-use behavior on the basis of TPB variables. P < 0.05 was considered as statistically significant. RESULTS: About 65% of respondents practiced "proper use" of helmets. Intention, perceived behavioral control (direct), and attitude (indirect) were significant predictors of helmet use (P < 0.05). Mean scores of knowledge on helmet use and behavior showed positive correlation (P > 0.05). CONCLUSIONS: Application of TPB in urban Indian context was successful in identifying precursors of helmet use. This study throws a light on the strong influencers of helmet use which can assist policy developers in developing effective programs to successfully promote the "proper use" of helmets.